Risk factors associated with facial fractures - Anne Margareth Batista; Fernanda de Oliveira Ferreira; Leandro Silva Marques; Maria Letícia Ramos-Jorge; Meire Coelho Ferreira (Brazilian Oral Research, 2012)
The aim of the present study was to identify risk factors for facial fractures in patients treated in the emergency department of a hospital. The medical charts of 1121 patients treated in an emergency ward over a three-year period were analyzed. The independent variables were gender, age, place of residence (urban or rural area) and type of accident. The dependent variables were fractured mandible, zygoma, maxilla, nasal bone and more than one fractured facial bone. Statistical analysis was performed using the chi-square test (a < 0.05), univariate and multivariate Poisson distributions and the logistic regression analysis (p < 0.20). Maxillofacial trauma was recorded in 790 charts (70.5%), with 393 (35.1%) charts reporting facial fractures. Motorcycle accidents were found to be the main risk factor for mandibular fractures (PR = 1.576, CI = 1.402-1.772) and simultaneous fractures of more than one facial bone (OR = 4.625, CI = 1.888-11.329) as well as the only risk factor for maxillary bone fractures (OR = 11.032, CI = 5.294-22.989). Fractures of the zygomatic and nasal bones were mainly associated with accidents involving animals (PR = 1.206, CI = 1.104-1.317) and sports (OR = 8.710, CI = 4.006-18.936), respectively. The determinant for the majority of facial fractures was motorcycle accidents, followed by accidents involving animals and sports.